ความสวยงามวางนัยทั่วไป: การเริ่มต้นของริงของจำนวนเศษเหลือ - ทองรักษ์, สุทิน; เอี่ยมพันธ์, อัยเรศ (Health Science, Science and Technology Reviews, 2014)
บทความนี้นำเสนอการศึกษาและการหาการดำเนินการทวิภาค ) บนเซตของจำนวนเศษเหลือ ZR โดย ผลการศึกษาพบว่า เป็นริง มากไปกว่านั้นยังพบว่า มีเอกลักษณ์ และสอดคล้องกับสมบัติการสลับที่ Generalized beauty: beginning of the ring of remainder numbers Suthin Thongrak1 and Aiyared Iampan1* 1 Department of Mathematics, School of Science, University of Phayao, Phayao Province 56000 This article presented the study and finding a binary operation ) on the set of remainder numbers ZR . The results showed that is a ring. Moreover, had an identity and satisfy the commutative property.